The oppressive legal status of the Sámi in Northwestern Russia - Ollila, Mirkka (Idäntutkimus, 2023)
This article focuses on the effects of the legal framework of the indigenous peoples of Russia in different aspects of the lives of the Sámi people of Kola. In Russia, the Constitution and the Federal Laws guarantee the protection of indigenous peoples’ way of life through various rights. Despite this, several scholars and the media have increasingly written about the challenges related to the realization of the rights of indigenous peoples, especially in the last decade. In the study, the effects of the rights of the Sámi are examined with the help of legal pluralism, taking into account the colonial nature of the laws and their end result. The research data consists of four interviews, 21 news articles from 2013-2022, and one podcast. The results show that the three spheres of influence of Sámi rights are: control of rights through self-government and self-determination; obstacles related to the pursuit of traditional livelihoods; and contradictions in the existence of rights de jure. The colonialist attitude of the Russian Federation towards its Arctic regions manifests itself in the primacy of the capitalist interest of the Kola Peninsula at the expense of the rights and traditions of the Sámi people. The research emphasizes the regressive effect of the Putin regime on the realization of indigenous rights. Consequently, the obstacles and effects of the exercise of Sámi rights are seen as intentional, oppressive, and suppressing the population. Tässä artikkelissa paneudutaan Venäjän alkuperäiskansojen oikeudellisen kehyksen vaikutuksiin Kuolan saamelaisten elämän eri osa-alueilla. Venäjällä sekä perustuslaki että liittovaltion lait takaavat alkuperäiskansojen elämäntavan suojelun erinäisten oikeuksien turvin. Tästä huolimatta useat tutkijat ja tiedotusvälineet ovat kirjoittaneet yhä enemmän alkuperäiskansojen oikeuksien toteutumiseen liittyvistä haasteista, etenkin viimeisen vuosikymmenen aikana. Tutkimuksessa saamelaisten oikeuksien vaikutuksia tarkastellaan laillisen moninaisuuden avulla ottaen huomioon ...